Proteksi Katodik Dengan Menggunakan Anoda Korban Pada Struktur Baja Karbon Untuk Mengendalikan Laju Korosi - Ian Desi Rosalina Situmeang; Komalasari Komalasari; Evelyn Evelyn (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pipes that are on land or at sea are generally made of steel which is susceptible to corrosion by the environment. The absence of control of the corrosion system metal structures directly related to the environment will be susceptible to corrosion. Prevention of corrosion in water and in the soil can use the principle of cathodic protection. Cathodic protection is a metal surface protection system by passing adequate direct current to the metal surface and converting all anode areas on the metal surface into cathodic regions. This research aims to study the effect of cathodic protection in controlling the corrosion rate of carbon steel, determine the best immersion time between the cathode and anode and choose the type of anode in its use to protect corrosion. The sample material used are low carbon steel with aluminum and zinc sacrificial anodes. The test solution used was a solution of Sodium Chloride with a concentration of 25,000 ppm then carried out by varying the immersion time of the anode and the cathode which were 10 days, 20 days, and 30 days with the distance of the anode to the cathode which was 3 cm. The results of the study using aluminum and zinc sacrificial anodes obtained the best results with a immersion time of 10 days where the corrosion rate of carbon steel protected by aluminum sacrificial anode was 1.596 mpy with an efficiency of 58.182% while the corrosion rate of carbon steel protected by anodes zinc sacrifice of 2.706 mpy with an efficiency of 29.091%.Keywords: carbon steel, cathodic protection, corrosion rate, electrode, sacrificial anode